2018
DOI: 10.1002/mrm.27596
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiac‐driven liver movements with filtered harmonic phase image representation, optical flow quantification, and motion amplification

Abstract: Purpose To characterize cardiac‐driven liver movements using a harmonic phase image representation (HARP) with an optical flow quantification and motion amplification method. The method was applied to define the cardiac trigger delay providing minimal signal losses in liver DWI images. Methods The 16‐s breath‐hold balanced‐SSFP time resolved 20 images/s were acquired at 3T in coronal and sagittal orientations. A peripheral pulse unit signal was recorded. Cardiac‐triggered DWI images were acquired after differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, cardiac-triggered DWI scans are associated with low acquisition efficiency and require the optimisation of the trigger delay at each individual subject [ 13 ]. In addition, it has been recently suggested that a single trigger delay might not be adequate for removing artifacts induced by cardiac motion and vessel pulsation throughout the whole liver [ 14 , 15 ]. Therefore, motion-compensated diffusion gradient encoding waveforms have recently been proposed as alternatives for motion-robust liver DWI [ 15 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, cardiac-triggered DWI scans are associated with low acquisition efficiency and require the optimisation of the trigger delay at each individual subject [ 13 ]. In addition, it has been recently suggested that a single trigger delay might not be adequate for removing artifacts induced by cardiac motion and vessel pulsation throughout the whole liver [ 14 , 15 ]. Therefore, motion-compensated diffusion gradient encoding waveforms have recently been proposed as alternatives for motion-robust liver DWI [ 15 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory-triggered scans are typically used to overcome subject respiratory motion both in the kidneys [1][2][3][4][5][6]8,9,13,[16][17][18] and other organs such as the liver [19][20][21][22][23][24]. Cardiac-triggered scans have also been proposed to overcome motion artifacts caused by cardiac driven pulsation [22,[25][26][27]. However, the low efficiency of simultaneous respiratory and cardiac-triggered DWI scans can make cardiac triggering impractical in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%